The Reception of Western Political Thought on the Forms of Government in Siam - ไชยภูมี เอกลักษณ์ (Journal of Letters, 2019)
This article outlines the reception of western political thought on the forms of government in Siam, which subsequently engendered political articulations and forced Siamese elites to adjust the structure of the government after the western model. This process can be categorized into two separate courses of action, which are the internal and external necessities laying conditions for Siamese elites to improve the political structure in order to survive by meeting the standard of civilization set by the European model, which itself has changed over time. The constraints from the western world during the colonization period, however, have forced the related actors in Siam to come up with explanations and reasoning to support their decision to overhaul the structure of the Siamese State following the adjusted western model, and one of the conspicuous indicators of this process of change within the Siamese government, this article argues, can be seen from the coinage and the conceptual change of basic words in politics, which are “Government”, “Monarchy”, and “Democracy” respectively. Lastly, this study limits the scope of study within the reign of King Rama IV to King Rama VII.